Handbook of Mathematical Models for Languages and Computation - Meduna, Alexander, 1957-; Horáček, Petr; Tomko, Martin (Professional applications of computing series ;, 2019)
The book comprises 20 chapters dealing with the following subjects: mathematical models for languages and computation; sets; sequences; relations; functions; graphs; classical models; finite automata; context-free grammars; pushdown automata; Turing machines; computability; decidability; context-dependent grammars; regulated models; parallel grammatical models; jumping models; deep pushdown automata; syntax analysis; programming languages; natural languages; and biology